Application of UAV in 3D Real-Scene Surveying and Mapping of Jilin West Railway Station - Shi, Yanqiu; Kong, Lingwei (Journal of Research in Science and Engineering, 2025)
Unmanned Aerial Vehicle (UAV) aerial surveying and mapping is an emerging technology with wide applications, playing a significant role in civil engineering. Compared with traditional surveying and mapping methods, UAV tilt photogrammetry technology is of great significance for reducing field survey personnel, surveying workload, and saving expenses on personnel and equipment. In this study, the DJI Phantom 4 RTK UAV was used for field surveys to obtain data and images of Jilin West Railway Station. DJI Terra 3D modeling software was employed to establish a 3D real-scene model, and the 3D Mapping Special Edition of eps2016 Geographic Information Workstation was utilized to draw 2D topographic maps (CAD) of the station. This work realizes the 3D real-scene construction of Jilin West Railway Station, a cultural relic protection building, explores the practical application of UAVs in the field of cultural relic protection, and practices the transformation path and implementation method of replacing the traditional measurement production system with a digital one.